2022
DOI: 10.3390/toxics10050215
|View full text |Cite
|
Sign up to set email alerts
|

Amino-Functionalized Polystyrene Nano-Plastics Induce Mitochondria Damage in Human Umbilical Vein Endothelial Cells

Abstract: As emerging contaminants, nano-plastics have become a major cause for concern for their adverse effects on the ecosystem and human health. The nano-sized properties of nano-plastics enable their exposure risks to humans through the food chain or other ways. However, the fate and adverse impact of nano-plastics on the human cardiovascular system are lacking. In this regard, the human umbilical vein endothelial cell line HUVEC was applied as a cell model to investigate the biological effects of noncharged polyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Having this in mind, NAC is expected to attenuate stressor induced oxidative stress due to its antioxidative properties. As polystyrene nanoparticle induced toxicity might be mediated by oxidative stress ( Fu et al, 2022 ), NAC is expected to rather mitigate any nanoparticle induced toxicity. Given the nanoparticle penetration enhancing property of NAC, the increased cytotoxicity values observed after NAC treatment might rather be attributed to an elevated exposure of cells to an increased number of particles.…”
Section: Resultsmentioning
confidence: 99%
“…Having this in mind, NAC is expected to attenuate stressor induced oxidative stress due to its antioxidative properties. As polystyrene nanoparticle induced toxicity might be mediated by oxidative stress ( Fu et al, 2022 ), NAC is expected to rather mitigate any nanoparticle induced toxicity. Given the nanoparticle penetration enhancing property of NAC, the increased cytotoxicity values observed after NAC treatment might rather be attributed to an elevated exposure of cells to an increased number of particles.…”
Section: Resultsmentioning
confidence: 99%
“…In line with our findings, a previous study in HUVEC cells, reported that PS‐NH 2 NPs affect the MMP more than plain PS NPs. [ 56 ] Another study in cells of the respiratory tract also detected mitochondrial damage upon treatment with PS‐NH 2 only but could also observe an increase in ROS production. [ 5 ] Different from our findings instead, previous work in other cell lines, have shown increased ROS production after treatment with PS NPs (40 nm), however used particles were slightly smaller and bought from a different manufacturer.…”
Section: Resultsmentioning
confidence: 99%
“…Huang et al 244 showed that decabromodiphenylethane and ZnO-NPs reduced mitochondrial membrane potential (MMP), increased cytochrome C release, and modulated Bax/Bcl-2 and cysteine by disrupting mitochondrial kinetic homeostasis Apoptosis was induced by the expression of dp-3 mRNA and protein. Fu et al 245 showed that amino-functionalized PS-NPs induced mitochondrial damage and decreased cell viability in human umbilical vein endothelial cells. This is consistent with the study by Li et al 246 that PS microplastics trigger mitochondrial damage and apoptosis through ROS-driven calcium overload.…”
Section: Studies Between Nps and Mitochondrial Damagementioning
confidence: 99%
“…Fu et al. 245 showed that amino‐functionalized PS–NPs induced mitochondrial damage and decreased cell viability in human umbilical vein endothelial cells. This is consistent with the study by Li et al.…”
Section: Toxicological Mechanisms Of Npsmentioning
confidence: 99%